Zadłużenie a nieodsetkowa tarcza podatkowa polskich spółek akcyjnych - Kościelniak, Helena (Indebtedness and Non-Interest Tax Target in Polish Joint Stocks Companies, 2005)
The article presents the results of empirical research showing the direction and strength of the dependence between the indebtedness rate and the level of non-interest tax target in Polish joint stock companies. The indebtedness rate is presented as the relation of general commitment and general assets. The measure of the non-interest tax target is the share of the amortization in the assets. Presented results of the research are part of the analysis of different elements which influence the indebtedness of the joint stock companies and aim at their activity financial supporting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 179-189